Book review: Droegemeier, Kelvin K. Demystifying the academic research enterprise: becoming a successful scholar in a complex and competitive environment - Elena Maceviciute (Information Research: An International Electronic Journal, 2024)
Droegemeier, Kelvin K. Demystifying the academic research enterprise: becoming a successful scholar in a complex and competitive environment. Cambridge, MA: The MIT Press, 2023. xxiv, 323 p. ISBN 978-0-262-54707-9